2017
DOI: 10.1177/0886260517719905
|View full text |Cite
|
Sign up to set email alerts
|

“How Many Silences Are There?” Men’s Experience of Victimization in Intimate Partner Relationships

Abstract: There is a substantive body of research focusing on women's experiences of intimate partner violence (IPV), but a lack of qualitative studies focusing on men's experiences as victims of IPV. This article addresses this gap in the literature by paying particular attention to hegemonic masculinities and men's perceptions of IPV. Men ( N = 9) participated in in-depth interviews. Interview data were rigorously subjected to thematic analysis, which revealed five key themes in the men's narratives: fear of IPV, main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
63
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 50 publications
(78 reference statements)
9
63
1
2
Order By: Relevance
“…Other concerns expressed by men that kept them from calling the police in cases of IPA were fears about the well-being of children affected by the arrest, financial issues, partner’s threats to destroy men’s lives, prior negative experiences with seeking help with the police, and other practical concerns. This is consistent with Brooks et al’s (2017) study that found limitations utilizing only a masculinity framework when explaining the complex experiences of male victims of IPA. Moreover, these barriers to help-seeking expressed by men in our study are similar to those reported by female victims of IPA (e.g., Scheffer Lindgren & Renck, 2008), which suggests the practical concerns associated with being a victim are likely shared across genders.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Other concerns expressed by men that kept them from calling the police in cases of IPA were fears about the well-being of children affected by the arrest, financial issues, partner’s threats to destroy men’s lives, prior negative experiences with seeking help with the police, and other practical concerns. This is consistent with Brooks et al’s (2017) study that found limitations utilizing only a masculinity framework when explaining the complex experiences of male victims of IPA. Moreover, these barriers to help-seeking expressed by men in our study are similar to those reported by female victims of IPA (e.g., Scheffer Lindgren & Renck, 2008), which suggests the practical concerns associated with being a victim are likely shared across genders.…”
Section: Discussionsupporting
confidence: 91%
“…A few men reported it would be unmanly to show injuries to the police and succumb to the role of a victim from the female partner. Prior research of gendered reactions to violence victimization had similar results (e.g., Brooks et al, 2017). These were not the only concerns that men expressed.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, hegemonic masculinities are not a fixed character type but a configuration of practices generated in particular situations in a changing structure of relationships (Connell, 2005). Hegemonic masculinity tends to involve a high degree of ruthless competition, an inability to express emotions other than anger, an unwillingness to admit weakness or dependency, devaluation of women and all feminine attributes in men, and homophobia, among other features (Brooks et al, 2020; Kupers, 2005). Thus, it is possible to argue that hegemonic masculinity is socially constructed in a manner that orients men’s perception of feeling vulnerable towards denying or suppressing their feelings.…”
Section: Introductionmentioning
confidence: 99%